Dynamic Mineralization: Low‐Temperature, Rapid, and Multidirectional Process to Encapsulate Polyether‐Ether‐Ketone with Carbonate‐Rich Hydroxyapatite for Osseointegration. Issue 15 (15th July 2021) - Lui, Florence H. Y.; Mobbs, Ralph J.; Wang, Yu; Koshy, Pramod; Lucien, Frank P.; Zhou, Dewen; Sorrell, Charles C.
Abstract: Polyether‐ether‐ketone (PEEK) is one of the key materials used to fabricate intervertebral spacers due to its mechanical similarity to bone and non‐interference with imaging. However, its surface chemistry limits osseointegration, while its chemical unreactivity and low glass transition/melting temperature poses technical challenges to the application of coatings conducive to bone growth. The present work applies nature‐inspired interfacial and surface chemistry processes to encapsulate PEEK with nanocrystalline carbonate‐rich hydroxyapatite (C‐Ap), a bioactive mineral valued for its chemical/structural similarity to bone mineral and its bioresorbability. This technique is distinguished from previous work by the combined features of low‐temperature, multidirectional/rapid application, and additive‐free processing. The resultant nanocrystalline C‐Ap coating encapsulates PEEK, indicating suitability with standard and state‐of‐the‐art spacers, made by additive/subtractive techniques. A precursor CaCO3 layer is deposited on PEEK by nacre‐inspired convective self‐assembly, followed by a travertine‐inspired rapid (10 min) cold‐sintering treatment. The CaCO3 layer is converted to C‐Ap in phosphate buffered saline through dissolution‐recrystallization processes inspired by the hydrated layer of bone. The coatings exhibit contact pressures that are an order of magnitude higher than coatings deposited by the biomimetic method. There is potential for application to other orthopaedic materials and incorporation of biologics throughout the coating structure for sustained release. Abstract : Dynamic mineralization is a low‐temperature, rapid, and multidirectional coating process that forms an encapsulating carbonate‐rich hydroxyapatite coating on polyether‐ether‐ketone, indicating suitability with complex structural features characteristic of next‐generation spacers made by additive/subtractive techniques. Its nanostructure exhibits outstanding tribological performance with contact pressures of ≈300 MPa to withstand frictional stresses characteristic of the spacer implantation process.